(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Technologies can be useful for dealing with emergencies such as that determined by CoViD-19. According to some studies, traditional contact tracing can be made more efficient and effective with the use of digital technologies. However, not everything that is technologically conceivable is also legally permitted (nor the consequent negative effects would be desirable). For this reason, it is necessary to establish a correct balance of rights to prevent a health emergency from turning into a democratic emergency. The article aims to examine how the use of technologies in the context of contact tracing can be done in compliance with European legislation on fundamental rights, including the General data protection regulation (GDPR).